High-efficiency mass transfer Malangori hydrogel reactor as well as preparation method and application thereof
By loading fuel and precious metal nanoparticles in cellulose hydrogel rotor, and using the Malaysigini effect to drive the rotation of the rotor, the existing water gel reactor has low quality transmission efficiency. method.
Patent Information
- Application Number
- CN202411498630.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing hydrogel reactors have low mass transfer efficiency during catalytic process, making it difficult to achieve high reaction rates, and the preparation method is complex and costly.
Using the Malaysgini hydrogel reactor, the reactor is loaded with fuel and precious metal nanoparticles in the cellulose hydrogel rotor, and uses the Malangguni effect to drive the rotation Quality and efficiency.
It significantly improves the contact efficiency between catalysts and the substrate, improves the catalytic response rate, the degradation rate can reach 99 %, and the preparation method is simple and the cost is low.
Smart Images

Figure CN119368114A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of reactors, and in particular to a Marangoni hydrogel reactor with high-efficiency mass transfer, a preparation method and an application thereof. Background Art
[0002] With the rapid development of the economy, organic pollutants in wastewater from various industries have seriously threatened the ecological environment and even human health. The problem of sewage discharge has attracted widespread attention from researchers. In recent years, nanomaterials, especially precious metal nanoparticles, have been widely used in the degradation of toxic organic pollutants and water quality remediation due to their unique physical and chemical properties, such as high catalytic performance, good selectivity and stability. Since precious metal nanoparticles are easy to agglomerate and difficult to recycle, they are often loaded on various carriers for catalytic reactions. For example, many inorganic and organic porous materials have been selected as carriers of precious metal nanoparticles. Among them, some natural polymers such as cellulose and lignin can be used as carriers of precious metal nanoparticles and as reducing agents.
[0003] By loading precious metal nanoparticles in cellulose-based hydrogels, efficient catalytic and stable reactors can be obtained. However, in practical applications, this loading also brings challenges to catalysis: the substrate in the reaction needs to penetrate the porous structure and liquid film on the surface of the carrier to enter the catalyst surface. Unfortunately, due to the lack of driving force, the transport of substances in ordinary reaction systems depends entirely on the concentration gradient, resulting in slow substrate diffusion and low reaction rate. Therefore, the hydrogel reactor prepared by the existing method is not sufficient to maintain high mass transfer efficiency during the catalytic process. The development of a more ideal and efficient mass transfer reactor and its application in the biotransformation of precious metal nanoparticles has become an urgent problem to be solved in this field.
[0004] In recent years, in order to increase the reaction rate, several methods of accelerating fluid movement have been proposed, such as stirred reactors, continuous fluid catalysis and interfacial self-propelled robots, which effectively enhance the mass transfer during the reaction process. For example, the Chinese invention with application number 202211616988.5 discloses a heterogeneous substrate enzyme catalytic reaction device and method with high-efficiency mass transfer. The method adopts a two-phase reverse feeding mixing method in a tower reactor with internal parts. However, the yield of the catalytic reaction product carried out in this reactor is only 56.1%. For example, the Chinese invention with application number 202410431144.6 discloses a continuous fluid method for macro-scale preparation of noble metal single-atom catalysts. The method transports the nitrogen-containing carbon-based carrier dispersion and the noble metal salt solution to the reactor through a pipeline at a certain flow rate in the same direction under the drive of a peristaltic pump for uniform mixing and reaction, which can effectively improve the contact efficiency between the two. However, this method requires additional instruments, such as mixers, infusion pumps and closed liquid pipes, which are complicated to operate and costly. Therefore, there is an urgent need to develop a simple and efficient method to effectively improve the catalytic efficiency by promoting the mass transfer between catalysts and substrates without the aid of complex equipment.
[0005] At the same time, interfacial self-propelled robots have broad application prospects in environmental monitoring, water treatment, liquid pumping and other fields. In recent years, inspired by insects, researchers have developed a series of Marangoni self-propelled interfacial robots driven by surface tension gradients. However, the existing Marangoni reactors cannot achieve the organic unity of simple preparation methods and strong power and long-term motion. For example, the Chinese invention with application number 202111125634.6 discloses the preparation and application of a light-responsive actuator based on the Marangoni effect. The actuator is mainly composed of a film made of a mixture of polydimethylsilane, carbon, and ferroferric oxide. The actuator only continues to move 150 mm within 90 seconds under the irradiation of a light source; another example is the Chinese invention with application number 202211447338.2. It discloses a graphene soft robot that can walk freely on the water surface and its preparation method. The soft robot is mechanically cut from a hydrophobic graphene film. The graphene film is obtained by synchronously reducing, cross-linking, and hydrophobic modification of graphene oxide at high temperature with silane vapor. The preparation method is cumbersome and the robot movement efficiency is low, and additional energy needs to be applied for driving. Therefore, the key technology that needs to be solved for reactors based on the Marangoni effect is to have a simple preparation method, sufficient power, and long-term movement. Summary of the invention
[0006] Purpose of the invention: The first purpose of the present invention is to provide a Marangoni hydrogel reactor with efficient mass transfer; the second purpose of the present invention is to provide a method for preparing the above reactor; the third purpose of the present invention is to provide an application of the above reactor.
[0007] Technical solution: The efficient mass transfer Marangoni hydrogel reactor provided by the present invention is a cellulose hydrogel rotor capable of producing the Marangoni effect and loaded with fuel, wherein the cellulose hydrogel rotor comprises a front end and a rear end, the front end is a cross-linked cellulose hydrogel, and the rear end is a cellulose hydrogel loaded with catalyst precious metal nanoparticles.
[0008] Furthermore, the fuel is isopropanol, n-propanol, hexafluoroisopropanol, ethanol, dimethyl sulfoxide or acetone.
[0009] Furthermore, the noble metal is palladium, silver or platinum.
[0010] The preparation method of the above-mentioned Marangoni hydrogel reactor comprises the following steps:
[0011] (1) mixing a cellulose solution and a noble metal salt solution, stirring and reducing them to obtain a cellulose mixed solution loaded with noble metal nanoparticles, and then injecting the mixed solution into a mold 1 capable of producing a Marangoni effect, and demolding after gelation to obtain a rear end of a cellulose hydrogel rotor;
[0012] (2) placing the rear end of the cellulose hydrogel rotor into a mold 2 capable of producing the Marangoni effect, then injecting the cross-linked cellulose solution into the remaining part of the mold 2, and soaking it in water after gelation to obtain a Marangoni cellulose hydrogel rotor;
[0013] (3) The Marangoni hydrogel rotor is immersed in fuel to obtain a fuel-loaded Marangoni cellulose hydrogel rotor, which is a Marangoni hydrogel reactor with efficient mass transfer.
[0014] Furthermore, in step (1), the preparation method of the cellulose solution is: dissolving cellulose in a mixed aqueous solution of sodium hydroxide and urea, and then homogenizing to uniformly disperse the cellulose to obtain a cellulose solution; the mass percentage of cellulose in the cellulose solution is 1-3wt%; the precious metal salt is palladium chloride, silver nitrate and chloroplatinic acid; and the molar concentration of the precious metal salt in the mixed solution is 2.4-20.5mmol / L.
[0015] Furthermore, in steps (1)-(2), the mold 1 for producing the Marangoni effect and the mold 2 capable of producing the Marangoni effect are both gear-like structures, including a gear ring and a plurality of gear teeth, the gear teeth being arranged on the outer edge of the gear ring, the gear ring being a disc-shaped structure, the cross-section of the gear teeth of the mold 1 being a triangular structure, the top angle being 20-30°, the length of one side of the gear teeth close to the gear ring being equal to the radius of the gear ring, and the cross-section of the gear teeth of the mold 2 being a special-shaped triangular structure with an arc-shaped outer edge, wherein the thickness of the gear ring is 2-4 mm, and the radius of the gear ring is 5-6 mm.
[0016] Further preferably, in mold 1 and mold 2, the thickness of the gear ring is 2 mm, the radius of the gear ring is 5 mm, the length of one side of the gear tooth close to the gear ring is 5 mm, the top angle of mold 1 is 25 degrees, and the outer side of mold 2 is a spline curve.
[0017] Furthermore, in step (2), the preparation method of the cross-linked cellulose solution is: adding epichlorohydrin to the cellulose solution and stirring sufficiently to obtain the cross-linked cellulose solution; wherein the mass of epichlorohydrin is 2-5wt% of the mass of the cellulose solution.
[0018] Furthermore, in step (3), the soaking time is 15-60 minutes.
[0019] The application of the above-mentioned Marangoni hydrogel reactor in the degradation of organic pollutants.
[0020] Furthermore, the application method is: placing a Marangoni hydrogel reactor in a solution containing organic pollutants, and the Marangoni hydrogel reactor performs a catalytic degradation reaction on the air-water interface by self-rotation; the molar concentration of the organic pollutants is 10mmol / L-50mmol / L; and the organic pollutants are dyes.
[0021] Invention principle: In the present invention, when cellulose changes from a sol state to a solid hydrogel, hydrogen bonds are re-formed between cellulose molecules. 2+ The reduction process leads to the reduction of -OH, which reduces the formation of hydrogen bonds in the cellulose chain, thus forming a loose microstructure. In contrast, during the chemical crosslinking process of the front hydrogel, the -OH on the cellulose chain is converted to C=O and COC, and a highly crosslinked three-dimensional porous network is formed. The asymmetric polymer network of the rotor constructed in this way will produce a significant gradient surface tension when the fuel is released, thereby generating sufficient power to achieve its high-speed spin. When the rotor is driven by the Marangoni effect, the rotating rotor can promote the disturbance of the fluid and the movement of the substrate therein. The rotation rate of the rotor is higher than the movement rate of the substrate. At the same time, the opposite movement direction between the precious metal loaded on the rotor and the substrate can promote the active contact between the two. In this case, the substrate will pass through the reactor pores faster to reach the catalyst surface, effectively improving the mass transfer efficiency; at the same time, the fluid disturbance driven by the rotor will cause the relatively distant substrate to be homogenized. When the substrate around the rotor is consumed, the distant substrate will accumulate around the catalyst faster, increasing the concentration gradient around the rotor, significantly accelerating mass transfer, and thus increasing the catalytic rate.
[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) In the reactor, cellulose forms loose and dense networks through reduction and cross-linking, respectively, thereby forming different structures of internal and external hydrogels, which can generate significant gradient surface tension when the fuel is released; MCR can achieve high-speed and long-term rotation (up to 7200r / h, rotation time greater than 25min), indicating that the reactor has sufficient and lasting power; (2) Experimental results show that the material movement generated by rotation can accelerate the entry of substrates into the reactor pores, while fluid disturbance can promote the replenishment of distant substrates around the catalyst, thereby improving the contact efficiency between the catalyst and the substrate and significantly improving the catalytic efficiency; kinetic results show that the kinetic constant of the Marangoni hydrogel rotor during rotation is 16.5 times that of the static porous hydrogel; based on this characteristic, the rotor can quickly decolorize MB and MO within 2.3min and 3.9min; the degradation rate of the dye is as high as 99%. In addition, after repeated recycling, the degradation rate of the dye to MB was still above 85%; (3) Due to its good hydrophilicity, the in situ addition of 80 μL of fuel can extend the rotor rotation time by 13 min; (4) The preparation method is easy to operate, low in cost, and has the potential for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a physical picture of the mold used in Example 1 of the present invention and the prepared Marangoni hydrogel reactor;
[0024] Figure 2 1 is an electron microscope image of the asymmetric cellulose polymer network of Example 1 of the present invention, a is an electron microscope image of the back-end polymer network, and b is an electron microscope image of the front-end polymer network;
[0025] Figure 3 is a speed and rotation time diagram of Examples 1 to 5 of the present invention;
[0026] Figure 4 Figure 1 is the change of absorbance over time during the degradation of MB to colorless in Example 1 (Figure a) and Comparative Example 1 (Figure b) of the present invention; Figure c is the time required for Example 1 to Example 4 and Comparative Example 1 to degrade MB to colorless and the time required for Example 5 to degrade MO to colorless;
[0027] Figure 5 It is a conceptual diagram of in-situ fuel dripping in Example 1 of the present invention (Figure a) and a statistical diagram of the rotation speed and rotation time after dripping (Figure b);
[0028] Figure 6 This is a kinetic calculation diagram after MB is catalyzed 5 times in the cycle of Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with specific embodiments and drawings.
[0030] Example 1: The efficient mass transfer Marangoni hydrogel reactor provided in this example is a cellulose hydrogel rotor capable of producing the Marangoni effect and loaded with fuel ethanol, wherein the cellulose hydrogel rotor comprises a front end and a rear end, the front end is a cross-linked cellulose hydrogel, and the rear end is a cellulose hydrogel loaded with palladium nanoparticles.
[0031] The preparation method of the Marangoni hydrogel reactor specifically comprises the following steps:
[0032] (1) dissolving cellulose in a mixed aqueous solution of sodium hydroxide and urea at -12.5°C, and homogenizing three times to uniformly disperse the cellulose to prepare a 2 wt% cellulose solution;
[0033] (2) mixing the cellulose solution of step (1) with a palladium chloride solution, wherein the palladium chloride is dissolved in a hydrochloric acid solution having a pH of 3 at 70° C., and then stirring the mixed solution at 60° C. for 4 h until it turns black, to obtain a cellulose mixed solution loaded with palladium nanoparticles, wherein the concentration of palladium chloride is 10.2 mM, and injecting the mixed solution into a mold 1, and demolding after gelation to obtain the rear end of the rotor;
[0034] (3) placing the rear end of the rotor obtained in step (2) into mold 2, adding epichlorohydrin in a mass ratio of 1:0.036 to the cellulose solution in step (1), stirring at 0° C. for 2 h to obtain a cross-linked cellulose solution, and then injecting the solution into the remaining part of mold 2. After gelation, soaking in water until there is no residue of sodium hydroxide urea solution to obtain a Marangoni cellulose hydrogel rotor;
[0035] (4) Soaking the hydrogel rotor obtained in step (3) in ethanol for 30 minutes to obtain a fuel-loaded hydrogel rotor, namely the Marangoni hydrogel reactor.
[0036] The application steps are: transferring the Marangoni hydrogel reactor into a 30 mmol / L MB dye solution to allow it to undergo a catalytic degradation reaction at the air-water interface.
[0037] Comparative Example 1 is used as a comparison. A porous hydrogel loaded with palladium catalyst is obtained by not performing the injection mold operation in step (2) and step (3) in Example 1. Specifically, the following steps are included:
[0038] (1) dissolving cellulose in a mixed aqueous solution of sodium hydroxide and urea at -12.5°C, and homogenizing three times to uniformly disperse the cellulose to prepare a 2 wt% cellulose solution;
[0039] (2) mixing the cellulose solution of step (1) with a palladium chloride solution, wherein the palladium chloride is dissolved in a hydrochloric acid solution having a pH of 3 at 70° C., and then stirring the mixed solution at 60° C. for 4 hours until it turns black, to obtain a cellulose mixed solution loaded with palladium nanoparticles, wherein the concentration of palladium chloride is 10.2 mM, and the mixed solution is refrigerated to form a gel to obtain a hydrogel loaded with a palladium catalyst;
[0040] (3) Place the rear end of the rotor obtained in step (2) into mold 2, add epichlorohydrin in a mass ratio of 1:0.036 to the cellulose solution in step (1), and stir thoroughly at 0°C for 2 hours to obtain a cross-linked cellulose solution. Then, refrigerate the solution to form a gel, first place the hydrogel in step (2), and soak it in water after gelation until there is no residue of sodium hydroxide urea solution to obtain a porous hydrogel loaded with palladium catalyst.
[0041] The application method is: transferring the porous hydrogel into a 30mmol / L MB dye solution to allow it to undergo a catalytic degradation reaction in the solution.
[0042] Example 2: The efficient mass transfer Marangoni hydrogel reactor provided in this example is a cellulose hydrogel rotor capable of producing the Marangoni effect and loaded with fuel ethanol, wherein the cellulose hydrogel rotor comprises a front end and a rear end, the front end is a cross-linked cellulose hydrogel, and the rear end is a cellulose hydrogel loaded with palladium nanoparticles.
[0043] The preparation method of the Marangoni hydrogel reactor specifically comprises the following steps:
[0044] (1) dissolving cellulose in a mixed aqueous solution of sodium hydroxide and urea at -12.5°C, and homogenizing three times to uniformly disperse the cellulose to prepare a 2 wt% cellulose solution;
[0045] (2) mixing the cellulose solution of step (1) with a palladium chloride solution, wherein the palladium chloride is dissolved in a hydrochloric acid solution with a pH of 3 at 70° C., and then stirring the mixed solution at 60° C. for 4 h until it turns black, to obtain a cellulose mixed solution loaded with palladium nanoparticles, wherein the concentration of palladium chloride is 2.4 mM, and injecting the mixed solution into a mold 1, and demolding after gelation to obtain a rear end hydrogel of the rotor;
[0046] (3) Place the rear end of the rotor obtained in step (2) into mold 2, add epichlorohydrin in a mass ratio of 1:0.072 to the cellulose solution in step (1), and stir at 0°C for 2 hours to obtain a cross-linked cellulose solution. Then inject the solution into the remaining part of mold 2, soak it in water after gelation until there is no residue of sodium hydroxide urea solution, and obtain a Marangoni cellulose hydrogel rotor;
[0047] (4) Soaking the hydrogel rotor obtained in step (3) in ethanol for 30 minutes to obtain a fuel-loaded hydrogel rotor, namely the Marangoni hydrogel reactor.
[0048] The application steps are: transferring the Marangoni hydrogel reactor into a 10 mmol / L MB dye solution to allow it to undergo a catalytic degradation reaction at the air-water interface, with the degradation rate reaching 99.9% within 3.5 minutes.
[0049] Example 3: The efficient mass transfer Marangoni hydrogel reactor provided in this example is a cellulose hydrogel rotor capable of producing the Marangoni effect and loaded with the fuel n-propanol, wherein the cellulose hydrogel rotor comprises a front end and a rear end, the front end is a cross-linked cellulose hydrogel, and the rear end is a cellulose hydrogel loaded with palladium nanoparticles.
[0050] The preparation method of the Marangoni hydrogel reactor with high mass transfer efficiency in this embodiment comprises the following steps:
[0051] (1) dissolving cellulose in a mixed aqueous solution of sodium hydroxide and urea at -12.5°C, and homogenizing three times to uniformly disperse the cellulose to prepare a 2 wt% cellulose solution;
[0052] (2) mixing the cellulose solution of step (1) with a palladium chloride solution, wherein the palladium chloride is dissolved in a hydrochloric acid solution with a pH of 3 at 70° C., and then stirring the mixed solution at 60° C. for 4 h until it turns black, to obtain a cellulose mixed solution loaded with palladium nanoparticles, wherein the concentration of palladium chloride is 20.5 mM, and injecting the mixed solution into a mold 1, and demolding after gelation to obtain a rear end hydrogel of the rotor;
[0053] (3) Place the rear end of the rotor obtained in step (2) into mold 2, add epichlorohydrin at a mass ratio of 1:0.09 to the cellulose solution in step 1, and stir at 0°C for 2 hours to obtain a cross-linked cellulose solution. Then inject the solution into the remaining part of mold 2, soak it in water after gelation until there is no residue of sodium hydroxide urea solution, and obtain a Marangoni cellulose hydrogel rotor;
[0054] (4) Soaking the hydrogel rotor obtained in step (3) in n-propanol for 10 minutes to obtain a fuel-loaded hydrogel rotor, namely the Marangoni hydrogel reactor.
[0055] The application steps are: transferring the Marangoni hydrogel reactor into a 35 mmol / L MB dye solution to allow it to undergo a catalytic degradation reaction at the air-water interface, with a degradation rate of 99.9% within 2.3 minutes.
[0056] Example 4: The efficient mass transfer Marangoni hydrogel reactor provided in this example is a cellulose hydrogel rotor capable of producing the Marangoni effect and loaded with fuel isopropanol, wherein the cellulose hydrogel rotor comprises a front end and a rear end, the front end is a cross-linked cellulose hydrogel, and the rear end is a cellulose hydrogel loaded with silver nanoparticles.
[0057] The preparation method of the Marangoni hydrogel reactor with high mass transfer efficiency in this embodiment comprises the following steps:
[0058] (1) dissolving cellulose in a mixed aqueous solution of sodium hydroxide and urea at -12.5°C, and homogenizing three times to uniformly disperse the cellulose to prepare a 3 wt% cellulose solution;
[0059] (2) mixing the cellulose solution of step 1 with the silver nitrate solution, and then stirring the mixed solution at 60° C. for 4 h until it turns black to obtain a cellulose mixed solution loaded with silver nanoparticles, wherein the concentration of silver nitrate is 5.1 mM, and injecting the mixed solution into mold 1, demolding after gelation, to obtain the rear end hydrogel of the rotor;
[0060] (3) Place the rear end of the rotor obtained in step (2) into mold 2, add epichlorohydrin in a mass ratio of 1:0.036 to the cellulose solution in step (1), and stir thoroughly at 0°C for 2 hours to obtain a cross-linked cellulose solution. Then inject the solution into the remaining part of mold 2, soak it in water after gelation until there is no residue of sodium hydroxide urea solution, and obtain a Marangoni cellulose hydrogel rotor;
[0061] (4) Soaking the hydrogel rotor obtained in step (2) in isopropanol for 20 minutes to obtain a fuel-loaded hydrogel rotor, namely the Marangoni hydrogel reactor.
[0062] The application steps are as follows: the Marangoni hydrogel reactor is transferred into a 40 mmol / L MB dye solution, so that it undergoes a catalytic degradation reaction at the air-water interface, and the degradation rate reaches 99.9% within 6.8 minutes.
[0063] Example 5: The efficient mass transfer Marangoni hydrogel reactor provided in this example is a cellulose hydrogel rotor capable of producing the Marangoni effect and loaded with the fuel hexafluoroisopropanol, wherein the cellulose hydrogel rotor comprises a front end and a rear end, the front end is a cross-linked cellulose hydrogel, and the rear end is a cellulose hydrogel loaded with platinum nanoparticles.
[0064] The preparation method of the Marangoni hydrogel reactor with high mass transfer efficiency in this embodiment comprises the following steps:
[0065] (1) dissolving cellulose in a mixed aqueous solution of sodium hydroxide and urea at -12.5°C, and homogenizing three times to uniformly disperse the cellulose to prepare a 2 wt% cellulose solution;
[0066] (2) the cellulose solution of step (1) is uniformly mixed with the chloroplatinic acid solution, and then stirred for 3 hours to obtain a cellulose mixed solution loaded with platinum nanoparticles, wherein the concentration of chloroplatinic acid is 15 mM, and the mixed solution is injected into mold 1, and demolded after gelation to obtain the rear end hydrogel of the rotor;
[0067] (3) Place the rear end of the rotor obtained in step (2) into mold 2, add epichlorohydrin at a mass ratio of 1:0.036 to the cellulose solution in step 1, and stir at 0°C for 2 hours to obtain a cross-linked cellulose solution. Then inject the solution into the remaining part of mold 2, soak it in water after gelation until there is no residue of sodium hydroxide urea solution, and obtain a Marangoni cellulose hydrogel rotor;
[0068] (4) Soaking the hydrogel rotor obtained in step (3) in hexafluoroisopropanol for 30 minutes to obtain a fuel-loaded hydrogel rotor, namely the Marangoni hydrogel reactor.
[0069] The application steps are: transferring the Marangoni hydrogel reactor into a 50 mmol / L MO (methyl orange) dye solution to perform a catalytic degradation reaction at the air-water interface, and the degradation rate reaches 99.9% within 3.9 minutes.
[0070] The materials prepared in Examples 1 to 5 and Comparative Example 1 were tested and characterized. The results are as follows: Figure 1-Figure 6 shown.
[0071] Figure 1 The following are pictures of the mold used in Example 1 and the resulting material. Figure 1 (a) is an optical image of the prepared rotor, which clearly shows that the rotor is composed of two different hydrogels. Figure 1 Figure (b1) in the figure is the mold 1 required for preparing the rear end hydrogel. Figure 1 Figure (b2) is the mold 2 required for preparing the front-end hydrogel. In molds 1 and 2, the thickness of the gear ring is 2 mm, the radius of the gear ring is 5 mm, and the length of the side of the gear close to the gear ring is 5 mm.
[0072] from Figure 2 It can be clearly seen that the Marangoni cellulose hydrogel rotor is composed of two different polymer networks. Figure 2 (a) is a SEM image of the rear end of the rotor. When cellulose changes from a sol state to a solid hydrogel, hydrogen bonds are re-formed between cellulose molecules. 2+ The reduction process leads to the reduction of -OH, which reduces the formation of hydrogen bonds in the cellulose chain, thus forming a loose microstructure. Figure 2(b) is the SEM image of the front section hydrogel, showing a large number of three-dimensional porous structures. This is because during the chemical cross-linking process, -OH is converted into C=O and COC, resulting in a high degree of cross-linking between cellulose chains to form a three-dimensional porous network. This asymmetric polymer network structure gives the rotor a significant gradient surface tension, allowing the rotor to rotate rapidly.
[0073] from Figure 3 It can be clearly seen that the hydrogel rotors loaded with different amounts of PdNPs have different effects on the rotor speed and rotation time due to their different porosities. Among them, the hydrogel rotor with a greater difference between the front and rear ends has a maximum speed of 6790r / h.
[0074] Figure 4 is the time required for Example 1 and Comparative Example 1 to degrade the dye MB, wherein Figure 4 (a) is Example 1, Figure 4 (b) is Comparative Example 1. It can be seen that the rotating rotor causes the absorbance of the dye to decrease rapidly, and the degradation rate reaches 99.9% within 4.5 minutes. However, the degradation rate of the dye by the static porous hydrogel lags far behind that of the rotating rotor, and it takes at least 20 minutes to reach 99.9%. Figure 4 (c) is the time required for the degradation of the corresponding dyes in Examples 1-5 and Comparative Example 1.
[0075] from Figure 5 It can be seen that due to the excellent hydrophilicity of cellulose materials, the in-situ dripping method greatly simplifies the steps of reloading the reactor with fuel and reduces fuel waste. Only dripping 80 μL of ethanol can make the MCR speed reach 4000 r / h again, and the endurance time can exceed 13.0 min.
[0076] from Figure 6 It can be seen that the rotor has good cycle stability, and the degradation rate of MB can still be maintained above 87% after five catalytic cycles, which is conducive to recycling.
Claims
1. A Marangoni hydrogel reactor with high mass transfer efficiency, characterized in that: The reactor is a cellulose hydrogel rotor capable of producing the Marangoni effect and loaded with fuel, wherein the cellulose hydrogel rotor comprises a front end and a rear end, the front end is a cross-linked cellulose hydrogel, and the rear end is a cellulose hydrogel loaded with catalyst noble metal nanoparticles.
2. The Marangoni hydrogel reactor according to claim 1, characterized in that: The fuel is isopropanol, n-propanol, hexafluoroisopropanol, ethanol, dimethyl sulfoxide or acetone.
3. The Marangoni hydrogel reactor according to claim 1, characterized in that: The noble metal is palladium, silver or platinum.
4. A method for preparing the Marangoni hydrogel reactor according to claim 1, characterized in that: The following steps are involved: (1) mixing a cellulose solution and a noble metal salt solution, stirring and reducing them to obtain a cellulose mixed solution loaded with noble metal nanoparticles, and then injecting the mixed solution into a mold 1 capable of producing a Marangoni effect, and demolding after gelation to obtain a rear end of a cellulose hydrogel rotor; (2) placing the rear end of the cellulose hydrogel rotor into a mold 2 capable of producing the Marangoni effect, then injecting the cross-linked cellulose solution into the remaining part of the mold 2, and soaking it in water after gelation to obtain a Marangoni cellulose hydrogel rotor; (3) The Marangoni hydrogel rotor is immersed in fuel to obtain a fuel-loaded Marangoni cellulose hydrogel rotor, which is a Marangoni hydrogel reactor with efficient mass transfer.
5. The preparation method according to claim 4, characterized in that: In step (1), the preparation method of the cellulose solution is: dissolving cellulose in a mixed aqueous solution of sodium hydroxide and urea, and then homogenizing to uniformly disperse the cellulose to obtain a cellulose solution; the mass percentage of cellulose in the cellulose solution is 1-3wt%; the noble metal salt is palladium chloride, silver nitrate and chloroplatinic acid; the molar concentration of the noble metal salt in the mixed solution is 2.4-20.5mmol / L.
6. The preparation method according to claim 4, characterized in that: In steps (1)-(2), the mold 1 for producing the Marangoni effect and the mold 2 capable of producing the Marangoni effect are both gear-like structures, including a gear ring and a plurality of gear teeth, the gear teeth are arranged on the outer edge of the gear ring, the gear ring is a disc-shaped structure, the cross-section of the gear teeth of the mold 1 is a triangular structure, the top angle is 20-30°, the length of one side of the gear teeth close to the gear ring is equal to the radius of the gear ring, and the cross-section of the gear teeth of the mold 2 is a special-shaped triangular structure with an arc-shaped outer edge, wherein the thickness of the gear ring is 2-4 mm, and the radius of the gear ring is 5-6 mm.
7. The preparation method according to claim 4, characterized in that: In step (2), the preparation method of the cross-linked cellulose solution is: adding epichlorohydrin to the cellulose solution and stirring thoroughly to obtain the cross-linked cellulose solution; wherein the mass of epichlorohydrin is 2-5wt% of the mass of the cellulose solution.
8. The preparation method according to claim 4, characterized in that: In step (3), the soaking time is 15-60 minutes.
9. Use of the Marangoni hydrogel reactor according to claim 1 in the degradation of organic pollutants.
10. The use according to claim 9, characterized in that: The application method is: placing the Marangoni hydrogel reactor in a solution containing organic pollutants, and the Marangoni hydrogel reactor performs a catalytic degradation reaction on an air-water interface through self-rotation.
Citation Information
Patent Citations
Graphene soft-bodied robot capable of freely walking on water surface and preparation method of graphene soft-bodied robot
CN115817734A
Optical driver based on Malangei effect
CN115877593A
Heterogeneous substrate enzyme catalytic reaction device and method with high mass transfer efficiency
CN117903932A
Continuous flow method for macroscopically preparing precious metal monatomic catalyst
CN118079991A
Preparation method of nanocellulose / metal particle composite aerogel
CN112029152A